2014
DOI: 10.1210/en.2013-1894
|View full text |Cite
|
Sign up to set email alerts
|

The Medio-Basal Hypothalamus as a Dynamic and Plastic Reproduction-Related Kisspeptin-gnrh-Pituitary Center in Fish

Abstract: Kisspeptin regulates reproductive events, including puberty and ovulation, primarily via GnRH neurons. Prolonged treatment of prepubertal striped bass females with kisspeptin (Kiss) 1 or Kiss2 peptides failed to enhance puberty but suggested a gnrh-independent pituitary control pathway. Kiss2 inhibited, but Kiss1 stimulated, FShβ expression and gonadal development, although hypophysiotropic gnrh1 and gnrh receptor expression remained unchanged. In situ hybridization and immunohistochemistry on brains and pitui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 60 publications
3
38
0
Order By: Relevance
“…This lack of differential GnRH1 and GnRH3 expression in face of downregulation of gonadotrophin b-subunit gene expression is surprising since it has been shown that neurons projecting from olfactory regions express GnRH1 and GnRH3 gene products (González-Martínez et al, 2001;Kah et al, 2007) and ablation of GnRH3 in zebrafish lead to reduced fecundity (Abraham et al, 2010). Our gene expression results for KISS2 and gonadotrophin b-subunits suggest a direct action of kisspeptin in the pituitary in this species, as had been suggested for rats, goldfish (C. auratus) and striped bass (Morone saxatilis) (Chang et al, 2012;Gutiérrez-Pascual et al, 2007;Zmora et al, 2014). In sea bass kiss2 neurons have been mapped mainly to the hypothalamus with projections to the subpallium and pallium, the preoptic region, the thalamus, the pretectal area, the optic tectum, the torus semicircularis, the mediobasal medial and caudal hypothalamus, and the neurohypophysis (Escobar et al, 2013a,b).…”
Section: Discussionsupporting
confidence: 53%
“…This lack of differential GnRH1 and GnRH3 expression in face of downregulation of gonadotrophin b-subunit gene expression is surprising since it has been shown that neurons projecting from olfactory regions express GnRH1 and GnRH3 gene products (González-Martínez et al, 2001;Kah et al, 2007) and ablation of GnRH3 in zebrafish lead to reduced fecundity (Abraham et al, 2010). Our gene expression results for KISS2 and gonadotrophin b-subunits suggest a direct action of kisspeptin in the pituitary in this species, as had been suggested for rats, goldfish (C. auratus) and striped bass (Morone saxatilis) (Chang et al, 2012;Gutiérrez-Pascual et al, 2007;Zmora et al, 2014). In sea bass kiss2 neurons have been mapped mainly to the hypothalamus with projections to the subpallium and pallium, the preoptic region, the thalamus, the pretectal area, the optic tectum, the torus semicircularis, the mediobasal medial and caudal hypothalamus, and the neurohypophysis (Escobar et al, 2013a,b).…”
Section: Discussionsupporting
confidence: 53%
“…Lh levels in the plasma were measured using ELISA as previously described (Mananos et al 1997). Levels of Fsh were measured using a specific ELISA developed for tilapia Fsh (Aizen et al 2007) and validated for use in STB (Zmora et al 2014). Gnrh decapeptide levels were measured using ELISA (Holland et al 1998, Zmora et al 2014.…”
Section: Hormones and Gene Transcript Measurementsmentioning
confidence: 99%
“…Levels of Fsh were measured using a specific ELISA developed for tilapia Fsh (Aizen et al 2007) and validated for use in STB (Zmora et al 2014). Gnrh decapeptide levels were measured using ELISA (Holland et al 1998, Zmora et al 2014. 11-Ketotestosterone (11-KT) levels in the plasma were measured using 11-KT EIA kit (Cayman Chemicals) according to the manufacturer's protocol.…”
Section: Hormones and Gene Transcript Measurementsmentioning
confidence: 99%
“…; Zmora et al . ). Genetic information has been restricted to a single‐tissue (ovary) transcriptome and a microsatellite linkage map from striped bass (Liu et al .…”
Section: Summary Of Trinity De Novo Assembly Results Of Illumina Rna‐mentioning
confidence: 97%